2000
DOI: 10.1007/s002940000147
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of laboratory mutants of Venturia inaequalis resistant to the strobilurin-related fungicide kresoxim-methyl

Abstract: Several agricultural fungicides related to the antifungal strobilurins act as inhibitors of respiration by binding to mitochondrial cytochrome b. Two types of laboratory mutants resisting higher doses of the strobilurin-related inhibitor kresoxim-methyl were characterized for Venturia inaequalis, the causal agent of apple scab. Selection of mutagenized conidia by kresoxim-methyl yielded mutants altered in the expression of alternative respiration during the stage of conidia germination. Cytochrome b sequences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 0 publications
3
70
0
2
Order By: Relevance
“…In this study, most resistant isolates showed a dominant homoplasmic population of A143 alleles. Zheng et al (2000) reported for V. inaequalis that cells with heteroplasmic cytochrome b alleles reverted rapidly to a more homoplasmic state, with mainly G143 alleles, without selection pressure of strobilurin fungicides. This indicates that a fitness penalty is associated with G143A in V. inaequalis.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this study, most resistant isolates showed a dominant homoplasmic population of A143 alleles. Zheng et al (2000) reported for V. inaequalis that cells with heteroplasmic cytochrome b alleles reverted rapidly to a more homoplasmic state, with mainly G143 alleles, without selection pressure of strobilurin fungicides. This indicates that a fitness penalty is associated with G143A in V. inaequalis.…”
Section: Discussionmentioning
confidence: 98%
“…For Venturia inaequalis (Zheng et al , 2000), Mycosphaerella fijiensis (Sierotzki et al , 2000a), B. graminis f.sp. tritici (Sierotzki et al , 2000b;Fraaije et al , 2000) and the oomycete Plasmopara viticola (Heaney et al , 2000), an exchange of glycine to alanine at position 143 (G143A) of the cytochrome b gene has been reported to confer high resistance levels to strobilurins.…”
Section: Accepted 3 August 2001mentioning
confidence: 99%
“…Currently, there are few studies monitoring sensitivity and early detection through the use of sentinel plants coupled with molecular detection in those instances where the mechanism can be detected, which could provide powerful information in an early warning system to anticipate the emergence of fungicide resistance in a population and prevent its occurrence. One problem with this approach is that most models for the detection of fungicide resistance emergence should assume an initial resistance mutation frequency from anywhere from as high as 10 -4 (Zwiers et al 2002) to as low as 10 -8 (Zheng et al 2000) based upon laboratory studies.…”
Section: Resultsmentioning
confidence: 99%
“…Preliminary data suggests that the populations in New York, Michigan and Indiana are not yet fixed (heteroplasmy). Laboratory analysis of QoI resistant mutants found that serial passage of trifloxystrobin-resistant isolates in vitro has resulted in a loss of resistance In V. inaequalis,after only two rounds of propagation allowed a significant majority of mitochondria containing the wild-type cytochrome b sequence to re-appear; This was not observed when the fungus was under continued selection (Zheng et al 2000) . The conversion of heteroplasmic isolates back to wild type in the absence of QoI fungicides would imply that a G143A mutation is associated with a fitness penalty, although Chapman et al (2011) found no evidence of this.…”
Section: Qoi-the Quinone Outside Inhibitorsmentioning
confidence: 99%
“…Two single nucleotide mutations of CYP51 resulting in amino acid substitutions Y136F and K147Q in Blumeria graminis were also found (Wyand & Brown, 2005). Different mutations were also found in Tapesia sp (Albertini et al, 2003), Penicillium italicum (Joseph-Horne & Hollomon, 1997), Ustilago maydis (Butters et al, 2000) and Blumeriella jaapii (Ma et al, 2006) Similarly, mutations have been described in the cytochrome b gene that lead to change of its corresponding protein G143A, conferring resistance to strobilurin (Avila-Adame & Koller, 2003aGisi et al, 2000, Zheng et al, 2000, Zhang, Z. et al, 2009 or the amino acid substitution in the -tubulin target protein involved in development of resistance to benzimidazoles in Botrytis cinerea (Banno, 2008), Venturia inaequalis and Penicillium italicum (Koenraadt et al, 1992), Monilinia fructicola , M. laxa (Ma & Michailides, 2005), P. expansum (Baraldi et al, 2003) and P. digitatum (Sánchez-Torres & Tuset, 2011).…”
Section: Changes In Binding Target That Causes a Reduced Affinity Ofmentioning
confidence: 88%